Prediction of Bending Beam Rheometer Test Outputs Using Artificial Neural Networks - Aljarrah, Mohammad Fuad; Alshorman, Mohammad Emad; Khasawneh, Mohammad Ali; Al-Omari, Aslam Ali (Key Engineering Materials IX - 9th International Conference on Key Engineering Materials (9th ICKEM 2019), 2019)
The major objective of this study is to investigate the possibility of using Artificial Neural Networks in creating prediction models capable of estimating Bending Beam Rheometer outputs; namely creep stiffness, and m-value based on test temperature, modifier content; in our case waste vegetable oil, and testing time interval. A feedforward backpropagation neural network with Bayesian Regulation training algorithm and an SSE performance function was implemented. It was found that the neural network model shows high predictive powers with training and testing performance of 99.8% and 99.2% respectively. Plots between laboratory obtained values and neural network predicted outputs were also considered, and a strong correlation between the two methods was concluded. Therefore, it was reasonable to state that using neural networks to build prediction models in order to find BBR test values is justified.